Increased Wnt and Notch signaling: a clue to the renal disease in Schimke immuno-osseous dysplasia?. Issue 1 (December 2016) - Morimoto, Marie; Myung, Clara; Beirnes, Kimberly; Choi, Kunho; Asakura, Yumi; Bokenkamp, Arend; Bonneau, Dominique; Brugnara, Milena; Charrow, Joel; Colin, Estelle; Davis, Amira; Deschenes, Georges; et al.
Abstract Background Schimke immuno-osseous dysplasia (SIOD) is a multisystemic disorder caused by biallelic mutations in theS WI/SNF-relatedm atrix-associateda ctin-dependentr egulator ofc hromatin, subfamilyA -l ike1 (SMARCAL1 ) gene. Changes in gene expression underlie the arteriosclerosis and T-cell immunodeficiency of SIOD; therefore, we hypothesized that SMARCAL1 deficiency causes the focal segmental glomerulosclerosis (FSGS) of SIOD by altering renal gene expression. We tested this hypothesis by gene expression analysis of an SIOD patient kidney and verified these findings through immunofluorescent analysis in additional SIOD patients and a genetic interaction analysis inDrosophila . Results We found increased expression of components and targets of the Wnt and Notch signaling pathways in the SIOD patient kidney, increased levels of unphosphorylated β-catenin and Notch1 intracellular domain in the glomeruli of most SIOD patient kidneys, and genetic interaction between theDrosophila SMARCAL1 homologueMarcal1 and genes of the Wnt and Notch signaling pathways. Conclusions We conclude that increased Wnt and Notch activity result from SMARCAL1 deficiency and, as established causes of FSGS, contribute to the renal disease of most SIOD patients. This further clarifies the pathogenesis of SIOD and will hopefully direct potential therapeutic approaches for SIOD patients.